The Relationship Between Knowledge with Covid-19 Vaccine Decisions - Cathryne, Joice; Hutapea, Adventina Delima; Nova, Fiorentina (Universitas Malahayati, 2023)
ABSTRACT On January 20, 2021, Covid-19 transmission reached 1.012.350 cases in 224 countries, with a Case Fatality Rate in Indonesia of 33.2%. Indonesia has ranked first in Asia due to a very large increase in Covid-19 cases. The spread of Covid-19 can be prevented by implementing health protocols and vaccination programs. Although vaccination is very important many people doubt it. Based on data, the first dose of vaccine in West Kalimantan only reached 14.5%. This study aims to determine the relationship between knowledge with Covid-19 vaccine decisions. This study used a quantitative descriptive method with univariate and bivariate data analysis techniques. The sample in this study was composed of 383 residents who live in Pontianak and were selected by purposive sampling methods. The instrument in this study used the Covid-19 knowledge questionnaire. The result of the study was that 70.5% of respondents had good knowledge, and 86.7% received the Covid-19 vaccine. 22.5% of respondents had fair knowledge, where 3.5% of respondents decided not to vaccinate, 27% of respondents had poor knowledge, and 7% of respondents decided not to vaccinate. There was a relationship between knowledge with Covid-19 vaccination decisions, as evidenced by the Chi-square test (p=0.001). Good knowledge will produce the right decision for someone to act. Keywords : Covid-19, Covid-19 Vaccines, Vaccination